Money and Betrayal: Perceptions of Alimony Fairness in Relation to Infidelity - Jessica Wery; Michael Kothakota (Journal of Financial Therapy, 2022)
Alimony is a contentious topic often argued over during a divorce. Individuals getting divorced seek fairness in an alimony settlement, but due to how laws are written this can seem arbitrary. Public policy suggests laws should reflect the suggestions of the people it affects. Thus, public perception of alimony fairness is an important component in the discussion of what is fair for spouses. In addition, infidelity in marriage might change how the public views what is fair. This study collected data from 1,285 individual United States participants. Participants were randomly assigned a vignette condition related to a hypothetical alimony scenario where one of the spouses had committed infidelity. Using logistic regression and multivariate Heckman selection models, we find when the higher wage earner has an affair, they are punished with a higher alimony amount for a longer period. Further, t-tests indicate that men are punished more than women. Finally, comparisons are made to three alimony formulas used across the United States. Financial therapists may be able to use this information to help divorcing couples separate the emotional aspect of an affair and the needs or ability to pay related to alimony. The results of this can be two-fold: keep the marital estate intact and help the couple heal emotionally.
Keywords: alimony; divorce; fairness; infidelity; selection bias